BUILDING ISLAMIC SCHOOLING IN A MUSLIM-MINORITY REGION: KH. USO, 'ASABIYAH, AND THE INSTITUTIONALIZATION OF ISLAMIC EDUCATION IN PAPUA (1965–2020) - Fauzi, Nasrul; rahmansyah, Abdur; Herlina, Herlina; Bahri, Azri; Faizah, Nur (Al-Qalam, 2025)
This research is historical research that explores the role of KH. Uso in establishing and developing Islamic education in Muslim minority areas in Southwest Papua, especially in Sorong City, through the stages of heuristic, criticism, interpretation and historiography. KH. Uso as a pioneer of Islamic education was commissioned by the Ministry of Religion in 1965, KH. Uso faced significant challenges in establishing Islamic educational institutions in the midst of the Christian majority. Using Ibn Khaldun's Ashabiyah theory, this research analyzes the social solidarity between the indigenous and migrant Muslim communities, which has become a significant force in the development of Islamic education in Papua. In addition, state support the Papua Special Autonomy policy and contribution from organizational networks such as Nahdlatul Ulama (NU) and Muhammadiyah also accelerated the process of Islamic education in the region. KH Uso succeeded in establishing various Islamic education institutions, such as PGAN, MI Annur YAPIS, STAIS Al Hikma, and STAIN Sorong, which provided access to formal Islamic education that was previously very limited. The results of this research show that although socio-political challenges and limited resources became obstacles, strong social solidarity and state support managed to overcome these difficulties. The thriving Islamic education in West Papua makes an important contribution to reducing the education gap between Muslims and the Christian majority and improving the overall quality of education.